2023
DOI: 10.3390/jcm12041512
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Helicobacter pylori Eradication Treatment on Metachronous Gastric Neoplasm Prevention Following Endoscopic Submucosal Dissection for Gastric Adenoma

Abstract: The long-term effect of Helicobacter pylori eradication on metachronous gastric neoplasm prevention after endoscopic submucosal dissection (ESD) of gastric adenoma is unclear. This study included patients with confirmed H. pylori infection after ESD with curative resection for gastric adenoma. Patients were divided based on the success of H. pylori eradication treatment into two groups: eradication and non-eradication. Patients with any newly detected lesion within 1 year after ESD and recurrence at the ESD si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…Recent largescale cohort studies showed a reduced risk of developing metachronous cancer (included in MSGENs) following Helicobacter pylori ( H. pylori ) therapy after endoscopic resection of early gastric cancer and adenoma [ 7 , 8 , 9 ]; therefore, H. pylori therapy is recommended for H. pylori -positive patients who have undergone ER of the superficial gastric epithelial neoplasms (SGENs). Contrastingly, other studies have reported that the risk of developing metachronous cancer does not decrease significantly after H. pylori therapy [ 5 , 6 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recent largescale cohort studies showed a reduced risk of developing metachronous cancer (included in MSGENs) following Helicobacter pylori ( H. pylori ) therapy after endoscopic resection of early gastric cancer and adenoma [ 7 , 8 , 9 ]; therefore, H. pylori therapy is recommended for H. pylori -positive patients who have undergone ER of the superficial gastric epithelial neoplasms (SGENs). Contrastingly, other studies have reported that the risk of developing metachronous cancer does not decrease significantly after H. pylori therapy [ 5 , 6 , 10 ].…”
Section: Introductionmentioning
confidence: 99%